The lost symbol - Brown, Dan (London : Corgi Books, 2009)
Harvard symbologist Robert Langdon is summoned unexpectedly to Washington, D.C., only to discover that a close friend has been kidnapped. As Langdon follows a series of coded clues hidden within the city$1 (Bs monuments and secrets, he becomes entangled in a race against time involving Freemasonry, ancient mysteries, and a deadly conspiracy threatening national security.s
Keywords: Langdon, Robert (Fictitious character) -- Fiction; Cryptographers -- Fiction; Freemasonry -- Fiction; Thrillers (Fiction).